2017
DOI: 10.1587/transinf.2016edp7473
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Community Detection in Social Network

Abstract: SUMMARYCommunity detection is a pivotal task in data mining, and users' emotional behaviors have an important impact on today's society. So it is very significant for society management or marketing strategies to detect emotional communities in social networks. Based on the emotional homophily of users in social networks, it could confirm that users would like to gather together to form communities according to emotional similarity. This paper exploits multivariate emotional behaviors of users to measure users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Regarding emotional flocking, past work found that people who express similarly valenced emotions on specific political topics were more frequently connected in network clusters on Twitter (Himelboim, Cameron, Sweetser, Danelo, & West, 2016;Yuan, Murukannaiah, Zhang, & Singh, 2014). More generally, online microblogging websites were argued to host emotion communities, which consist of interconnected users who are characterized by similar patterns of emotion expressions (Bollen et al, 2011;Zhu, Wang, Wu, & Zhang, 2017). The question of how far such communities are based on homophily versus emotional contagion (e.g., elicited by highly connected users) often remains unaddressed.…”
mentioning
confidence: 99%
“…Regarding emotional flocking, past work found that people who express similarly valenced emotions on specific political topics were more frequently connected in network clusters on Twitter (Himelboim, Cameron, Sweetser, Danelo, & West, 2016;Yuan, Murukannaiah, Zhang, & Singh, 2014). More generally, online microblogging websites were argued to host emotion communities, which consist of interconnected users who are characterized by similar patterns of emotion expressions (Bollen et al, 2011;Zhu, Wang, Wu, & Zhang, 2017). The question of how far such communities are based on homophily versus emotional contagion (e.g., elicited by highly connected users) often remains unaddressed.…”
mentioning
confidence: 99%
“…Consequently, the study identified the influence of each user to detect influential communities for which they use a modularity-based community detection algorithm [41]. Zhu, et al [42] also supposed that user emotions can affect the formation of a community. They investigated this issue in three phases: (i) they created an emotional network, (ii) they applied the CNM and BGLL algorithms to detect communities in the emotional network, and (iii) they compared their results with those of four other networks to verify their method.…”
Section: B Dynamic Algorithmsmentioning
confidence: 99%
“…The detected communities may reveal important structural properties of the underlying system. Community detection has been used in diverse areas including, discovering potential friends on social networks 7 , evaluating social networks 8 , personalized recommendation of item to user 9 , detecting potential terrorist activities on social platforms 10 , fraud detection in finance 11 , study epidemic spreading process 12 and so on.…”
Section: Introductionmentioning
confidence: 99%